Accuracy of foot length measurement for gestational age assessment in neonates: a prospective observational study in Central India - Singhal, Asmita; Agrawal, Avyact; Parihar, Rashmi; Sahu, Nency; Upadhyay, Jaya (International Journal Of Community Medicine And Public Health, 2024)
Background: Gestational age (GA) is a critical-factors in the decision making and predicting mortality and morbidities of neonates. In low resource settings where affordability and availability of first trimester scan is limited, assessment is often done by postnatal methods like expanded new Ballard score (ENBS) which are often clinical skill dependent and complex. Hence, there is a need of a simple and cost-effective method which can be readily adopted by frontline health care workers at periphery. One such method is assessment of foot length (FL). Methods: This prospective cross-sectional study was conducted in the level 3 NICU of Central India over a period of 18 months. Included neonates were assessed for GA by measuring FL by vernier calliper within 48 hours of birth and its validity was tested against ENBS as reference standard. Other anthropometric measurements like birth weight, head circumference and length were obtained within 48 hours of birth. Results: Total 700 neonates were included in the study. For, determining preterm newborn, the potential cut-off of FL of ≤6.86 cm, with a sensitivity of 94.6% and specificity of 73.8%. The area under ROC (receiver operating characteristic) curve is 0.92. Conclusions: FL measurement is a cost-effective and time-saving simple intervention that can facilitate early identification of preterm newborns as well as help in initiating timely interventions and hence improving neonatal outcomes in resource-poor settings.